Examination into the effects of job satisfaction on salesperson deviance: The moderating role of customer orientation - Lo Iacono, Joseph; Weaven, Scott K.; Griffin, Deborah (Journal of Business Economics and Management, 2016)
Salesperson deviance represents a significant cost to organizations throughout the world. This paper addresses a gap in the literature by examining all three dimensions of salesperson deviance (i.e., organizational deviance, interpersonal deviance and customer-directed deviance) and the moderating role of customer orientation. More specifically and using a sales personnel sample, this research extends current understanding of deviant behavior in two key areas. Our findings show (1) a negative relationship between job satisfaction and each dimension of salesperson deviance, and (2) customer orientation moderates the relationship between job satisfaction and salesperson deviance. Thus, we present a more holistic view of salesperson deviance and, in practical terms, confirm that organizational stakeholders should proactively manage the job satisfaction together with the customer orientation of their sales staff in order to avoid and/or minimize deviant behaviors.